Democracy and famine - Rubin, Olivier (Routledge research in comparative politics ;, 2011)
Famine is the most extreme manifestation of the existence of poverty, inequality and political apathy. Whereas poverty, hunger and diseases are not easily eradicated in the world today, famines are often perceived to be relatively simple to avert. However, the political incentives to prevent famines are not always present. Inspired by the work of Amartya Sen, whose influential hypothesis that democratic institutions together with a free press provide effective protection from famine, Democracy and Famine is a study combining qualitative and quantitative evidence, analysing t.